AMINO-FORMALDEHYDE RESINS. PROPERTIES AND APPLICATION TO REMOVE CONTAMINANT METAL IONS. AN OVERVIEW - Bernabe L Rivas; Esteban Martinez (Journal of the Chilean Chemical Society, 2020)
The global production of formaldehyde urea resins (UF) for 2019 was 6 million ton/year, being the largest use in the forestry industry in the production of MDP and MDF boards. It is in the resin industry's interest to develop other applications of these polymers.The possible metal ion separation properties of commercial resins of the type urea-formaldehyde resins (UF), melamine-urea-formaldehyde resins (MUF), and formaldehyde melamine (MF) are achieved by modifying with functional groups.The metal retention properties are determined by batch method in aqueous phase where the purified and sieved solid resin is put into contact with the metal ions at different pH, controlling temperature and ion force. The most studied metal ions are metal ions like Cu(II), Co(II), Cd(II), Zn(II), Cr(III), Hg(II) and Cr(VI).The aim to contribute with this overview, is demonstrate the use of these modified resins to remove metal ions and also the potential application to use them as support to include new functional groups to increase the efficiency and affinity, Moreover, it is motivated by the production in our country of these resins and investigate possible applications in this research field.